2011
DOI: 10.1007/s00415-011-6335-z
|View full text |Cite
|
Sign up to set email alerts
|

The association of systemic lupus erythematosus and myasthenia gravis: a series of 17 cases, with a special focus on hydroxychloroquine use and a review of the literature

Abstract: The coexistence of systemic lupus erythematosus (SLE) and myasthenia gravis (MG) is rarely reported, and most of the published studies are case reports. Hydroxychloroquine, an antimalarial agent, is an essential treatment in patients with SLE but special caution is recommended when used in MG patients. We retrospectively analyzed the clinical features, laboratory findings, and outcome of 17 patients with both diseases with a special focus regarding hydroxychloroquine use and with a review of the literature. Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
64
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(73 citation statements)
references
References 60 publications
2
64
0
2
Order By: Relevance
“…Previous reports suggested that in a majority of the patients, MG preceded SLE [5]. Our patients had SLE when the MG diagnosis was made except one patient who had lupus-like symptoms without fulfilling the diagnostic criteria before MG onset.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Previous reports suggested that in a majority of the patients, MG preceded SLE [5]. Our patients had SLE when the MG diagnosis was made except one patient who had lupus-like symptoms without fulfilling the diagnostic criteria before MG onset.…”
Section: Discussionmentioning
confidence: 95%
“…Jallouli et al reported the co-occurrence of MG with SLE in 17 patients; they did not comment on the course of MG [5]. We would like to underline that all of our patients had generalized MG and four of five patients experienced at least one myasthenic crisis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Među pacijentima obuhvaćenim našom studijom, autoimune bolesti koje su se najčešće javljale udružene sa MG bile su Hašimoto tireoiditis, SLE, polimiozitis, RA i perniciozna anemija, što je u skladu sa nalazima drugih studija (9,15,23,25,26). Učestalost Hašimoto tireoiditisa iznosila je 4%, a skoro isti podatak (4,2%), dobijen je u studiji sprovedenoj u Japanu na 142 pacijenta sa MG (24).…”
Section: Diskusijaunclassified
“…Učestalost Hašimoto tireoiditisa iznosila je 4%, a skoro isti podatak (4,2%), dobijen je u studiji sprovedenoj u Japanu na 142 pacijenta sa MG (24). Zapažene učestalosti SLE u literaturi variraju od 1 do 8%, što je u skladu sa našim rezultatom od 1,3%, dok je učestalost udruženog javljanja RA u našoj studiji bila manja u odnosu na podatke iz drugih studija (0,9% naspram 4%) (9,15,23,25,26). Suzuki i saradnici (27) zabeležili su učestalost polimiozitisa od 0,65%, što je približno vrednosti od 0,9%, dobijenoj u našoj studiji.…”
Section: Diskusijaunclassified